Ultraviolet Fluorescence Spectra of Fingerprints - Naoki Saitoh; Norimitsu Akiba (The Scientific World Journal)
We have studied inherent fluorescence spectra and imaging of fingerprints in the deep ultraviolet (UV) region with a nanosecond-pulsed Nd-YAG laser system that consists of a tunable laser, a cooled CCD camera, and a grating spectrometer. In this paper, we have studied UV fluorescence spectra of fingerprints under 266-nm illumination. Fluorescence spectra of fingerprints have two main peaks, around 330 nm (peak A) and 440 nm (peak B). At first, when a fingerprint has just been pressed, peak A is dominant. However, its intensity reduces as the total illumination time increases. On the other hand, peak B is weak at first. It appears after enough 266-nm illumination and its intensity increases as time elapses. After 3 h of illumination, peak A almost diminishes and peak B becomes dominant. By leaving the fingerprint under a fluorescent lamp in a room without laser illumination, peak A can be restored partly, while the intensity of peak B still increases.Time-resolved fluorescence spectra were also measured for these two peaks. The lifetime of each peak is 2.0 nsec (peak A) and 6.2 nsec (peak B) on average. Both peaks seem to consist of several components with different lifetimes. In the case of peak A, the 330-nm peak decays fast and a new component at 360 nm becomes dominant when the delay time exceeds 20 nsec. In the case of peak B, unlike peak A, no clear peak separation is observed, but the peak position seems to move from 440 to 460 nm when the delay time becomes larger.